Efektivitas Pembelajaran Berbasis Masalah Berbantuan Media PAPSI Terhadap Keterampilan Komunikasi Siswa di Sekolah Dasar - Ika Fitria Jayanti; Husama Husama Husama (UMSU, 2023)
This study aims to improve the learning outcomes and communication skills of fifth grade students on fraction material in learning mathematics through the Problem Based Learning (PBL) model with the help of PAPSI at Elementary school. The research method used is Classroom Action Research (CAR) using two cycles. The research sample was fifth grade students at Elementary school. Data collection techniques were carried out using learning achievement tests and observation of communication skills. The results showed that the PBL model with the help of PAPSI could improve the learning outcomes and communication skills of fifth grade students in mathematics learning. In cycle I, the average student learning outcomes reached 88 with communication skills of 78 %. Whereas in cycle II, the average student learning outcomes increased to 96 with communication skills reaching 98 %. Therefore, it can be concluded that the PBL model with the help of PAPSI is effective in improving the learning outcomes and communication skills of fifth grade students on fraction material in learning mathematics.